Defaults change choices, not minds: Practical and ethical benefits of brief educational boosts for water recycling acceptance - Braden Tanner; Edward T. Cokely; Adam Feltz (Judgment and Decision Making, 2025)
Although nudges have been shown to influence many choices, it is possible that nudging may also result in undesirable consequences compared to other choice architectures (e.g., educational boosts). Here, we present evidence of one such case involving recycled water acceptance. In two experiments, we compared the effects of a popular nudge (i.e., defaults designed to increase acceptance) with an educational boost (e.g., a brief video designed to support informed decision making). Results revealed that both defaults and educational boosts substantially increased choices related to recycled water acceptance (e.g., >60% increase in enrollment in a hypothetical recycled water program across experiments). However, the educational boost also promoted choice-consistent effects on attitudes, intentions, and knowledge, while default nudges resulted in attitude inconsistency (e.g., expressing worry about recycled water; intending to protest and avoid water recycling). Results add to research on practical and ethical risks of nudging and the potential benefits of comparing the costs of nudges with other options.